2009
DOI: 10.11606/issn.1678-4456.bjvras.2009.26785
|View full text |Cite
|
Sign up to set email alerts
|

Meloxicam e prednisona: efeitos do tratamento oral de curto prazo sobre os níveis de pressão intra-ocular em cães

Abstract: ResumoPara possível observação da hipertensão ocular com o uso de antiinflamatórios, foram selecionados 28 cães da raça Beagle. Para avaliação da pressão intra-ocular antes do tratamento, no dia 0 (zero) todos os animais tiveram a pressão intra-ocular avaliada às 08 horas e às 16 horas. No dia seguinte dez cães receberam meloxicam na dose de 0,2 mg/kg, e 0,1mg/kg nos restantes quatro dias. Nove cães receberam prednisona na dose de 1,0 mg/kg durante cinco dias. Nove cães receberam somente porção de ração úmida.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Corticosteroids —Corticosteroid-induced IOP elevation is relatively common in humans, presumably related to lowered aqueous humor outflow from the deposition of extracellular material in the trabecular meshwork [ 51 ]. In contrast, most corticosteroids do not appear to influence IOP in dogs, including hydrocortisone [ 52 ], prednisone [ 53 ], prednisolone acetate [ 54 ], triamcinolone acetonide [ 55 ], and difluprednate [ 56 ]. For triamcinolone acetonide, intravitreal injection of the long-acting corticosteroid did not induce sustained IOP elevation over 3 months of monitoring IOPs [ 55 ].…”
Section: Anti-inflammatory Therapy For Eyes Predisposed or Affected B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroids —Corticosteroid-induced IOP elevation is relatively common in humans, presumably related to lowered aqueous humor outflow from the deposition of extracellular material in the trabecular meshwork [ 51 ]. In contrast, most corticosteroids do not appear to influence IOP in dogs, including hydrocortisone [ 52 ], prednisone [ 53 ], prednisolone acetate [ 54 ], triamcinolone acetonide [ 55 ], and difluprednate [ 56 ]. For triamcinolone acetonide, intravitreal injection of the long-acting corticosteroid did not induce sustained IOP elevation over 3 months of monitoring IOPs [ 55 ].…”
Section: Anti-inflammatory Therapy For Eyes Predisposed or Affected B...mentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs) —Orally administered carprofen or meloxicam did not influence IOP in normal dogs [ 53 , 59 ]. However, a study of topical flurbiprofen showed IOP elevation in dog eyes [ 60 ], presumably due to greater resistance in aqueous humor outflow [ 61 ]; in fact, immediate postoperative use of topical flurbiprofen may be a potential risk factor for the development of glaucoma following phacoemulsification in dogs [ 62 ].…”
Section: Anti-inflammatory Therapy For Eyes Predisposed or Affected B...mentioning
confidence: 99%